2021
DOI: 10.3390/vaccines9101146
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Clinical and Economic Outcomes Associated with Adjuvanted versus High-Dose Trivalent Influenza Vaccine among Adults Aged ≥ 65 Years in the US during the 2019–20 Influenza Season—A Retrospective Cohort Analysis

Abstract: The burden of influenza is disproportionally higher among older adults. We evaluated the relative vaccine effectiveness (rVE) of adjuvanted trivalent (aIIV3) compared to high-dose trivalent influenza vaccine (HD-IIV3e) against influenza and cardio-respiratory disease (CRD)-related hospitalizations/ER visits among adults ≥65 years during the 2019–2020 influenza season. Economic outcomes were also compared. A retrospective cohort analysis was conducted using prescription, professional fee claims, and hospital da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 25 publications
(69 reference statements)
0
10
0
8
Order By: Relevance
“…Four studies [28][29][30][31] were identified from the published systematic review. The remaining four studies/effect estimates [32][33][34][35] were identified via the targeted review, two of which were not yet published as of the time of the analysis. As the relative vaccine effectiveness of aTIV vs. HD-TIV may be expected to vary based on the characteristics of the study (e.g., influenza season, population included, outcome definition, etc.…”
Section: Vaccine Effectivenessmentioning
confidence: 99%
“…Four studies [28][29][30][31] were identified from the published systematic review. The remaining four studies/effect estimates [32][33][34][35] were identified via the targeted review, two of which were not yet published as of the time of the analysis. As the relative vaccine effectiveness of aTIV vs. HD-TIV may be expected to vary based on the characteristics of the study (e.g., influenza season, population included, outcome definition, etc.…”
Section: Vaccine Effectivenessmentioning
confidence: 99%
“…Fifteen studies reported the economic burden of seasonal influenza in adults aged [? ]65 years (28,34,35,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). The majority of studies (n=7) were conducted in the US (34,(41)(42)(43)(44)(45)(46).…”
Section: Economic Burdenmentioning
confidence: 99%
“…]65 years (28,34,35,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). The majority of studies (n=7) were conducted in the US (34,(41)(42)(43)(44)(45)(46). Very few studies were conducted in other countries of interest, including Spain (n=2) (50,51), China (n=1) (47), France (n=1) (48), Germany (n=1) (49), the UK (n=1) (28), Japan (n=1) (52), and South Africa (n=1) (35).…”
Section: Economic Burdenmentioning
confidence: 99%
“…Following the removal of duplicates (n = 226), a total of 857 records were screened by title and/or abstract and 841 papers were judged clearly ineligible. Of 16 full texts evaluated, 9 (Boikos et al, 2021;Izurieta et al, 2019;Izurieta et al, 2020;Izurieta et al, 2021;Levin et al, 2021;Machado et al, 2021;Pelton et al, 2020;Pelton et al, 2021;van Aalst et al, 2020) were included in the study, while 7 were excluded with reasons (Supplementary Table S3). The updated search identified another relevant study (Imran et al, 2022).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…No studies were identified through manual search. In summary, 10 peerreviewed articles (Boikos et al, 2021;Imran et al, 2022;Izurieta et al, 2019;Izurieta et al, 2020;Izurieta et al, 2021;Levin et al, 2021;Machado et al, 2021;Pelton et al, 2020;Pelton et al, 2021;van Aalst et al, 2020) underwent both qualitative and quantitative syntheses. Supplementary Figure S1 depicts the whole study selection process.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%